Expression of herpes simplex virus type 1 latency-associated transcripts in the trigeminal ganglia of mice during acute infection and reactivation of latent infection. - Spivack, J G (1988)
Herpes simplex virus type 1 (HSV-1) establishes a latent infection in the trigeminal ganglia of mice infected via the eye. In these ganglia three viral transcripts, of 2.0, 1.5, and 1.45 kilobases (kb), which are at least partially colinear, have been identified by Northern (RNA) blot analysis. These RNAs partially overlap ICPO, but are transcribed in the opposite direction (J. G. Spivack and N. W. Fraser, J. Virol. 61:3841-3847, 1987). The accumulation of these latency-associated transcripts, as well as other viral RNAs, was studied during an acute infection and the reactivation of a latent HSV-1 infection in mice. The 2.0-kb latency-associated transcript was detected in trigeminal ganglia of mice as early as 4 days postinfection, and the 1.45- and 1.5-kb RNA doublet was detected at 14 days postinfection. The levels of these latency-associated transcripts increased steadily over a 60-day period. In contrast, other HSV-1 transcripts were detected at 2 to 3 days postinfection, reached a peak on day 4, and rapidly declined below detectable levels by day 7. The data indicate that the temporal expression of the latency-associated genes during acute infection in the trigeminal ganglia of mice is different from the temporal expression of genes involved in HSV-1 replication. During the reactivation of latent HSV-1 from explanted trigeminal ganglia, the latency-associated RNAs decreased about twofold, but were present at significant levels even after HSV-1 DNA increased and infectious virus was recovered. The decrease of the latency-associated transcripts occurred when reactivation was blocked by phosphonoacetic acid or novobiocin, which suggests that this decrease may be an early event in the entry of latent HSV-1 into the viral replication cycle.